The relationship between human rights and refugee protection: an empirical analysis. Issue 10 (26th November 2021) - Abdelaaty, Lamis
ABSTRACT: What is the relationship between a government's respect for the rights of its own citizens and that government's regard for refugee rights? On one hand, we may expect that a country with high human rights standards will also offer a higher quality of asylum. Domestic laws that protect citizens' rights may be extended to refugees, for example. On the other hand, there are reasons to theorize that a country with high human rights standards may offer a lower quality of asylum. For instance, governments may claim that protecting citizens' wellbeing necessitates the rejection of refugees. To explore these questions, I analyse a global dataset drawn from reports by the US Committee for Refugees and Immigrants. I find that the relationship between citizens' rights and refugee rights is modified by economic conditions and the size of the refugee population. Moreover, some domestic rights (like freedom of movement and labor rights) may increase protections for refugees, while others (like rule of law) may decrease them. Refugees have been largely absent from the literature on the politics of human rights. By systematically examining the relationship between human and refugee rights worldwide, this paper fills an important gap in the scholarly and policy literature.